Urea Fertilizer for Bangladesh Challenges and Opportunity (Journal of Chemical Engineering, 2012)
The outlook for Urea Fertilizer at present and in coming years for Bangladesh-is a very much concerned issue and studied in the paper. The urea production vs. design capacity of all Fertilizer Plants and consumption has been shown. Main constraint for reduced urea production is identified as Natural gas shortage. To meet countries demand, the possibility of import from global urea supply and its impact on economy is also studied. Analyzing all the above; support to Urea Fertilizer factories- to ensure food security of the country - has been emphasized. Daily Natural Gas requirement for maintaining urea production is estimated. DOI: http://dx.doi.org/10.3329/jce.v26i1.10177 JCE 2011; 26(1): 22-26